PERWUJUDAN KESANTUNAN TINDAK TUTUR DIREKTIF BAHASA INDONESIA DALAM PELAYANAN KESEHATAN DI KALANGAN MASYARAKAT MULTIKULTURAL: SEBUAH TINJAUAN SOSIOPRAGMATIK - Tri Pujiati, _ (2020)
Differences in cultural and linguistic backgrounds in health services that occur in multicultural societies are the main issues in this study. This study seeks to resolve these cultural and linguistic differences by analyzing the politeness of directive speech acts in Indonesian. The aim is to find and describe the manifestation of politeness in the Indonesian language directive speech acts used by speakers in health services among multicultural communities. This research is a case study in certain multicultural communities in the realm of health services. This study uses a sociopragmatics approach and language politeness. This research uses a mixed method design with concurrent embedded models to interpret data. The research data were obtained using the DCT (Discourse Completion Test). A test complementing discourse was given to 60 respondents who are a reflection of a multicultural society. The results show that to overcome differences in cultural and language backgrounds in multicultural societies, respondents use language politeness choices according to the Indonesian cultural context by using linguistic politeness markers, such as "sorry, beg, please, come, and please" and use of culturally appropriate greetings. Indonesian culture. Respondents chose to use negative politeness strategies as an effort to protect the patient's face and to produce a high level of politeness. The findings based on the results of quantitative data processing in this study support the findings of qualitative research. The findings research show that there is an influence of social variables such as gender, health insurance, educational background, and age of the speaker, as well as the gender of the speaker on the level of politeness and strategy of directive speech act politeness in health services. This is in line with the findings of qualitative research that considers social status in using the Indonesian language directive speech act politeness strategy. The main variable that most influences the choice of courtesy of directive speech acts is the speaker's age so that the speakers must consider these social variables appropriately. Based on these findings, it can be formulated that the realization of directive speech act politeness in health services is adjusted to the characteristics of the patient's social status so that communication can run smoothly and problems related to differences in cultural backgrounds in multicultural societies can be resolved.